2021
DOI: 10.1186/s12967-021-02912-4
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 complete genome sequencing from the Italian Campania region using a highly automated next generation sequencing system

Abstract: Background Since the first complete genome sequencing of SARS-CoV-2 in December 2019, more than 550,000 genomes have been submitted into the GISAID database. Sequencing of the SARS-CoV-2 genome might allow identification of variants with increased contagiousness, different clinical patterns and/or different response to vaccines. A highly automated next generation sequencing (NGS)-based method might facilitate an active genomic surveillance of the virus. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The available literature shows the full-genome sequences can be obtained even from samples with less than 100 viral RNA copy number per reaction by analogous workflows (Ion AmpliSeq SARS-CoV-2 Research Panel and Ion Torrent Genexus Integrated System) [28]. This is just below the lowest number of viral RNA copies for which we have obtained high-quality results (156 viral RNA copies per reaction, sample 365; see Table S5).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The available literature shows the full-genome sequences can be obtained even from samples with less than 100 viral RNA copy number per reaction by analogous workflows (Ion AmpliSeq SARS-CoV-2 Research Panel and Ion Torrent Genexus Integrated System) [28]. This is just below the lowest number of viral RNA copies for which we have obtained high-quality results (156 viral RNA copies per reaction, sample 365; see Table S5).…”
Section: Discussionmentioning
confidence: 75%
“…Consistent with our study are findings by Jacot et al [29] who suggest C T ≥ 30 (78 or less of viral RNA copy number per reaction) can serve as an initial sequencing success predictor. An analysis comparing the Ion AmpliSeq Panel and Illumina-MiSeq ARCTIC Protocol showed both methods are overall equally effective, with the automation of all steps of library preparation within the TFS solution considered a strong advantage [30], which was expressed also by Rachiglio et al [28]. In the beforementioned study [30], one low-quality sample (C T 32,5) achieved 89% coverage with MiSeq-based ARCTIC pipeline, while it failed with the SARS-CoV-2 AmpliSeq Research panel, suggesting the TFS solution may be inferior to the MiSeq-based one in cases of low-template material.…”
Section: Discussionmentioning
confidence: 92%
“…This report includes a review of the first cases profiled using a novel highly automated gene sequencing system [13]. The automated nature of this system enables its use directly within a diagnostic histopathology laboratory, eliminating transfers of specimens and reports.…”
Section: Introductionmentioning
confidence: 99%
“…Plitnick et al, 2021, directly compared the performance of the SARS-CoV-2 AmpliSeq Research Panel to the results obtained with the Illumina MiSeqbased ARTIC Next ow analysis pipeline (30). Post-bioinformatic analysis of data from such studies showed that both methods produced similar levels of coverage (> 98%) across a broad range of viral loads (Ct values of 15.56 to 32.54 [median, 22.18]) and that both approaches sequenced SARS-CoV-2 effectively (30,32). Although the bioinformatic analysis pipelines used in this study differ, the ndings of our study are similar to those documented in the above study by Plitnick et al, 2021.…”
Section: Discussionmentioning
confidence: 99%